A Rapid Molecular Test for Determining Yersinia pestis Susceptibility to Ciprofloxacin by the Quantification of Differentially Expressed Marker Genes - Steinberger-Levy, Ida; Shifman, Ohad; Zvi, Anat; Ariel, Naomi; Beth-Din, Adi; Israeli, Ofir; Gur, David; Aftalion, Moshe; Maoz, Sharon; Ber, Raphael (Frontiers in Microbiology, 2016)
Standard antimicrobial susceptibility tests used to determine bacterial susceptibility to antibiotics are growth dependent and time consuming. The long incubation time required for standard tests may render susceptibility results irrelevant, particularly for patients infected with lethal bacteria that are slow growing on agar but progress rapidly in vivo, such as Yersinia pestis. Here, we present an alternative approach for the rapid determination of antimicrobial susceptibility, based on the quantification of the changes in the expression levels of specific marker genes following exposure to growth-inhibiting concentrations of the antibiotic, using Y. pestis and ciprofloxacin as a model. The marker genes were identified by transcriptomic DNA microarray analysis of the virulent Y. pestis Kimberley53 strain after exposure to specific concentrations of ciprofloxacin for various time periods. We identified several marker genes that were induced following exposure to growth-inhibitory concentrations of ciprofloxacin, and we confirmed the marker expression profiles at additional ciprofloxacin concentrations using quantitative RT-PCR. Eleven candidate marker transcripts were identified, of which four mRNA markers were selected for a rapid quantitative RT-PCR susceptibility test that correctly determined the Minimal Inhibitory Concentration (MIC) values and the categories of susceptibility of several Y. pestis strains and isolates harboring various ciprofloxacin MIC values. The novel molecular susceptibility test requires just 2 h of antibiotic exposure in a 7-h overall test time, in contrast to the 24 h of antibiotic exposure required for a standard microdilution test.